Coupling VIPs and ABPs: Assessment of Overall Thermal Performance in Building Wall Insulation. (November 2015) - Lorenzati, Alice; Fantucci, Stefano; Capozzoli, Alfonso; Perino, Marco
Abstract: Super Insulating Materials (SIMs) such as Vacuum Insulation Panels (VIPs) and Aerogel Based Products (ABPs), are characterised by lower thermal conductivities if compared with traditional insulating materials. The objective of the present work is to suggest a new technical solution to reduce the thermal bridging effects in buildings SIMs assemblies. A typological façade where VIPs and ABPs are coupled was numerically analysed to assess the global average thermal transmittance. Moreover results were compared with common solutions based on VIPs coupled with traditional insulating materials (EPS, MDF), considering both thermal and economic aspects.